Proceedings of Seventh International Conference on Bio-Inspired Computing: Theories and Applications (BIC-TA 2012) Volume 2 - Bansal, Jagdish Chand; Singh, Pramod; Deep, Kusum; Pant, Millie; Nagar, Atulya; SpringerLink (Online service) (India : Springer India : Imprint: Springer, 2013)
The book is a collection of high quality peer reviewed research papers presented in Seventh International Conference on Bio-Inspired Computing (BIC-TA 2012) held at ABV-IIITM Gwalior, India. These research papers provide the latest developments in the broad area of "Computational Intelligence". The book discusses wide variety of industrial, engineering and scientific applications of nature/bio-inspired computing and presents invited papers from the inventors/originators of novel computational techniques.
Preface -- Table of Contents -- About the Editors -- Organizing Committee -- Papers -- Author Index.
Keywords: Engineering; Data mining; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery